A Case Report: Angiomatoid Fibrous Histiocytoma in a 6-year-old Male and Review of the Literature. (1st June 2014) - Kaygusuz, Ecmel Isik; Cetiner, Handan; Yorganci, Cuma; Celayir, Aysenur
<x xml:space="preserve">Abstract</x> Angiomatoid Fibrous Histiocytoma (AFH) is a distinctive tumor in children, adolescent and young adults which is slow growing with metastatic potential. The histogenesis of AFH is uncertain. Here, we present a case of AFH of 6-year-old on the trunk. In addition, the differential diagnosis for this lesion is also discussed.